Hypolipidemic and Adipose-reducing Effects of Ethanolic Extract of Ziziphus Talanai (Blanco) Merr. in Monosodium Glutamate-Induced Obese Female Albino Rats - Maria Anabelle A. Samson; Lourdes Fatima S. David; Glen S. Nolasco; John Dave Dicuangco; Marilyn S. Arcilla (Research Synergy Foundation, 2024)
Obesity is a global health-related risk factor associated with metabolic disorders characterized by excessive fat accumulation and high lipid serum profile. One major factor contributing to obesity is the chronic consumption of monosodium glutamate (MSG). Generally, this study aimed to evaluate the hypolipidemic and anti-adipogenic effects of Ziziphus talanai ethanolic leaf extract (ZTELE) in MSG-induced obesity in female albino rats. A total of twelve (12) female albino rats were used in the study and divided into four treatment groups: T (distilled water), T+ (simvastatin), T1 (400 mg/kg ZTELE), and T2 (800 mg/kg ZTELE). Before treatment, rats were fed a high-fat diet and MSG for 1 month to induce obesity. Significant reductions in body weight, intrascapular and visceral fats, and selected lipid serum profiles (total cholesterol, high-density lipoproteins, low-density lipoproteins) were observed in the ZTELE-treated groups (T1 and T2), with comparable results to those of simvastatin-treated (T+). Phytochemicals, such as flavonoids, saponins, and tannins, influence metabolic pathways by their antioxidative potential, inhibition of lipid synthesis, and regulation of fat cell differentiation. In conclusion, ZTELE is a promising natural therapeutic agent for managing obesity by regulating fat accumulation and lipid metabolism.